Energy storage systems based on endoskeleton structuring. Issue 34 (10th August 2016) - Nam, Inho; Park, Jongseok; Bae, Seongjun; Park, Soomin; Yoo, Young Geun; Yi, Jongheop
Abstract : The new energy storage technology proposed here includes an endoskeleton architecture similar to vertebrates, which (1) provides flexibility for future mobile/human integrated electrics, (2) ensures the scalability of devices for the storage of fluctuating energy sources and (3) solves safety issues associated with energy storage devices in electric vehicles. Abstract : As electronic devices have continued to advance, consistent with Moore's law, it is clear that the development of technology can create new types of products and jobs and even industrial sectors. While human integrated devices, storage of fluctuating energy sources and electric transports are required in the near future, one field of electronics has not fully developed, – i.e., energy storage devices. In order to overcome this impediment, we developed a new approach of energy systems that is inspired by the difference in evolutionary genealogy between animals, i.e., insects (exoskeleton) versus vertebrates (endoskeleton). The new energy storage technology proposed here includes an endoskeleton architecture similar to vertebrates, which (1) provides flexibility for future mobile/human integrated electrics, (2) ensures the scalability of devices for the storage of fluctuating energy sources and (3) solves safety issues associated with energy storage devices in electric vehicles.